Dynamics of Self-Optimisation: An Introduction - Daniel Nehring (Historical Social Research, 2024)
This introduction explores the increasing pervasiveness of discourses and practices of selfoptimisationin present-day societies. These are evident in activities such as self-tracking, fitness training, cosmetic surgery, neuroenhancement, or the consumption of nutritional supplements. The growing appeal and diffusion of these various practices testifies to the overall cultural attraction of self-optimisation, which is a multifaceted phenomenon. Against the dominant interpretation of self-optimisation as mainly driven by the logic of maximisation and growth, we argue that it can also be about minimalism or balance. At the same time, self-optimisation is strongly connected to dynamics of power andsocial inequality, potentially reinforcing existing social inequalities and creating new forms of domination and control. The paper starts by charting the existing research and theoretical approaches to self-optimisation, presents the contributions to the special issue, addresses a set of key domains of selfoptimisation (therapeutic culture, health and well-being, digital technologies, work, and economy), and finally draws conclusions and suggests some avenues for future research.